Positive Margin Re-Excision Following Immediate Autologous Breast Reconstruction: Morbidity, Cosmetic Outcome, and Oncologic Significance. (17th March 2017) - Ochoa, Oscar; Theoharis, Constantine; Pisano, Steven; Chrysopoulo, Minas; Ledoux, Peter; Arishita, Gary; Nastala, Chet
Abstract: Background: Acquisition of negative resection margins is paramount in the surgical management of operable breast cancer. Management of positive margins following mastectomy and immediate breast reconstruction is presently poorly defined. Objectives: The present study aims at defining morbidity and cosmetic sequela of re-excision procedures aimed at clearing involved mastectomy margins in the setting of immediate autologous breast reconstruction. Oncologic outcomes are recorded. Methods: A retrospective study of patients that underwent skin-sparing mastectomy followed by immediate deep inferior epigastric perforator flap breast reconstruction was performed. Patients found to have positive mastectomy margins underwent margin re-excision during a separate procedure. Method of positive margin exposure and resection is described. Flap morbidity and cosmetic outcome following margin re-excision was compared between reconstructed breasts that underwent re-excision vs those reconstructed after prophylactic mastectomy (controls). Cancer recurrence was recorded during the follow-up period. Results: Thirty-six (2.5%) out of 1443 patients were found to have positive mastectomy margins following immediate breast reconstruction between May 2007 and November 2012. Location of positive margins was evenly distributed in all breast regions. Although flap morbidity was similar, a trend ( P > 0.05) toward higher seroma formation and fat necrosis was reported in breasts following re-excision vs controls. With a mean follow-up period of 28 months, cosmetic outcome between breasts that underwent re-excision vs controls were similar. Cancer recurrence was reported in 3 (8.3%) patients. Conclusions: Re-excision of positive mastectomy margins following immediate autologous breast reconstruction requires a multidisciplinary approach and may be performed with minimal additional morbidity while preserving optimal cosmetic outcome. Level of Evidence: 3: